The Effect of Bank Health on Profitability and Firm Value of Islamic Banks in Indonesia - Andriani, Andriani; Abarahan, Anmisuhailah binti (Equilibrium: Jurnal Ekonomi Syariah, 2023)
This study aims to determine the effect between bank health on profitability and firm value of Islamic Commercial Banks in Indonesia. This research employs a quantitative approach. Researchers conducted tests through the SPSS application and path analysis. The research included a total of 12 Islamic Commercial Banks for the financial year 2020-2022. The findings of this research demonstrate that RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) have a simultaneous impact on bank health, specifically on profitaility through Return on Assets (ROA). Partially, only payments affect ROA. Meanwhile, other indicators of RGEC do not affect ROA. Partially, risk profile and earnings indicators affect Return on Equity (ROE). In contrast, two other indicators, namely good corporate profile and capital, do not affect ROE. Simultaneously, the influence of bank health on firm value is mediated by RGEC. Partially, the four RGEC indicators have no impact on firm value. In other tests, through the mediation flow, neither ROA nor ROE can mediate the effect of RGEC on firm value. Meanwhile, profitability through ROA and ROE affects firm value. The implications of this research significantly contribute to understanding the financial stability of bank health, its effect on profitability, its effect on firm value, and its contributions to the field of academic research.